Synthesis, Characterization, Electrochemical, and Optic Limiting Properties of Novel CoII, CuII, and Double-Decker LuIII Phthalocyanines - Saydam, Sinan; Yilmaz, Engin; Bagci, Fulya; Yaglioglu, H. Guel; Elmali, Ayhan; Salih, Bekir; Bekaroglu, Ozer (Wiley-V C H Verlag Gmbh, 2009)
The synthesis, spectroscopic, electrochemical, and optical properties of tetrasubstituted Co-II, Cu-II, and double-decker Lu-III phthalocyanines are reported. The new compounds were characterized by elemental analysis, IR and UV/Vis spectroscopy, and MALDI TOF mass spectrometry. Their electrochemistry was studied by cyclic voltammetry and Osteryoung square-wave voltammetry in nonaqueous medium. Nonlinear absorption and optical limiting performance of peripheral-substituted (C30H28N30)(4)Co (5), (C30H28N30)(4)-Cu (6), and [(C30H28N30)(4)](2)Lu (7) were investigated by the Z-scan technique. Whereas 6 and 7 showed good nonlinear absorption, 5 did not. Optical limiting parameters of the ratio of the excited state to the ground state absorption cross sections K, the effective nonlinear absorption coefficient beta(eff), the linear absorption coefficient a(0), limiting threshold F-th, and the saturation density or energy density F-sat values were determined for 6 and 7. The results indicated that both compounds exhibited good optical limiting performances. ((C) Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2009)
Keywords: Phthalocyanines; Sandwich complexes; Electrochemistry; Nonlinear optics; Rare earths